The development of Analytical Thinking Skill Mathematics Subject of Grade 6 Students through Brain Based Learning with Mind Mapping - ทำคาม ภัทราพร; สลีวงศ์ ดนุชา; สุวรรณฉาย ศักดิ์ (Ratchaphruek Journal, 2018)
ABSTRACT The research purpose was to development analytical thinking skill through brain based learning with mind mapping of 6th graders. The sample was 33 students from 5 schools, which were Bankoknoi School, Bankuschool, Bannadonbok School, Banhongchangnoi School, and Banthonghlangnoi School. They were selected by cluster random sampling. The research instruments used in this research were: 1) 9lesson plans (16 hours) using brain based learning with mind mapping, and 2) an analytical thinking skill test. The statistics used to analyze the data were mean, standard deviation, repeated measure ANOVA. The findings showed that 6th graders through brain based learning with mind mapping has analytical thinking skill each time different at the 0.05 level of significance, they were considered the students’ analytical thinking skill was increasingly higher in each test from the first one to the last one at the 0.05 level of significance.